Inventory of labour market policy measures in the EU 2008-13: the crisis and beyond. Synthesis report - Gama, André; Saget, Catherine; Eyraud, François (Geneva, 2015)
"The “Inventory of labour market policy measures in the EU 2008-13: The crisis and beyond” report studies the way in which the labour market policies of Member States of the European Union evolved after the financial crisis of 2007/08, and the extent to which those policies were successful in mitigating the negative impact the crisis had on their labour markets.